Peningkatan Produksi Produk Pertanian Unggulan Lokal melalui Pengembangan Teknologi dan Manajemen Produksi Sirup Nenas Desa Rimbo Panjang Kecamatan Tambang Kabupaten Kampar - Bunga Chintia Utami; Julita Julita; Deby Kurnia; Rahmat Junaidi (Unri Conference Series: Community Engagement, 2025)
According to data from the Outlook of the Ministry of Agriculture of the Republic of Indonesia, a pineapple surplus is projected to reach 789.03 thousand tons in 2025 (Center for Agricultural Data and Information Systems, Ministry of Agriculture, 2023). High pineapple production without adequate downstream processing may lead to oversupply, short shelf life, price decline, and increased agricultural waste. One of the downstreaming efforts has been implemented by the “Nenas Berduri” (Ponari) Group in Rimbo Panjang Village, Kampar Regency, through pineapple syrup production. However, the group faced several key issues: low extraction yield due to manual equipment, absence of standardized operational procedures, and limited understanding of proper production techniques. This community empowerment program aimed to enhance production capacity and product quality through the introduction of processing technology, the development of standard operating procedures, and production training. The results showed an increase in production capacity from 20–30 bottles to 80–90 bottles per month, a reduction in extraction time from 5–6 hours to less than 1 hour per batch, and all group members were able to independently operate the juicing machine and apply the SOPs correctly. This activity contributed to improving production efficiency and group self-reliance, strengthening local MSME capacity, and supporting the sustainability of pineapple syrup as a regional flagship product.